Antibody-mediated delivery of VEGF-C promotes long-lasting lymphatic expansion that reduces recurrent inflammation - Cousin, Nikola; Bartel, Sophie; Scholl, Jeannette; Tacconi, Carlotta; Egger, Annina; Thorhallsdottir, Gudrun; Neri, Dario; Dieterich, Lothar; Detmar, Michael (Cells, 2023)
The lymphatic vascular system plays a fundamental role in inflammation by draining interstitial fluid, immune cells, antigens, and inflammatory mediators from peripheral tissues. Site-specific delivery of the lymphangiogenic growth factor VEGF-C alleviates acute inflammation in mouse models of psoriasis and chronic colitis by enhancing local drainage. However, it is unclear whether therapeutically induced lymphangiogenesis is transient or long-lasting and whether it might prevent relapses of inflammation. Here, we investigated the long-term effects of targeted VEGF-C delivery in a chronic dermatitis model in mice. Congruent with our previous results, intravenous injection with a VEGF-C fusion protein targeted to the EDA domain of fibronectin initially resulted in reduced inflammation. Importantly, we found that targeted VEGF-C-mediated expansion of lymphatic vessels in the skin persisted for more than 170 days, long after primary inflammation had resolved. Furthermore, the treatment markedly decreased tissue swelling upon inflammatory re-challenge at the same site. Simultaneously, infiltration of leukocytes, including CD4+ T cells, macrophages, and dendritic cells, was significantly reduced in the previously treated group. In conclusion, our data show that targeted delivery of VEGF-C leads to long-lasting lymphatic expansion and long-term protection against repeated inflammatory challenge, suggesting that it is a promising new approach for the treatment of chronic, recurrent inflammatory diseases.